Effectiveness of Environmental Law Implementation: Compliance and Enforcement - Dyah Mustika Prasetyaningsih; Eko Hendarto; Nurul Anwar; Khalid Eltayeb Elfaki (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2022)
Environmental permits or approvals as part of environmental law enforcement have a strategic role as instruments for preventing environmental pollution and damage. To determine the effectiveness of environmental law enforcement, it is necessary to measure the extent to which legal regulations are complied with or not complied with. This study aims to determine the level of compliance of business actors/activities in environmental management and monitoring based on environmental permit/approval commitments. The research method used is descriptive quantitative research; with type of research is empirical juridical. The research location is focused on the Kebumen Regency, Central Java. The number of samples in this study were 34 business actors from various sectors and were taken using the Herry King Nomogram with an error rate of 10%. Determination of the level of obedience using the scoring of each indicator. There are 17 indicators measured and modified from the Regulation of the Minister of Environment and Forestry Number 1 of 2021. The study results show the level of obedience of business actors or activities in the Kebumen Regency is dominated by the non-compliant and disobedient category with a percentage of 62% or 21 business actors/activities. The business/activity sectors in the disobedient and disobedient categories include trade, industry, mining, energy, health service facilities and tourism facilities. Business actors in the obedient category own 38% or 13 business actors/activities. The business/activity sectors in the compliant category include health service facilities, industry and energy. The government can determine priority steps in environmental monitoring based on the level of compliance of business actors. Monitoring efforts can then be followed up with strict and sustainable enforcement of environmental law.